Psicoanálisis, higienismo y eugenesia: educación sexual en Chile, 1930-1940 - Silvana Vetö (Nuevo mundo - Mundos Nuevos, 2014)
This work aims to elucidate some aspects of the reception of psychoanalysis in Chile that have not been brought to the forefront so far in its official history: the knots established by psychoanalysis with other discourses of the time, hygienism and eugenics. These knots are addressed in a cultural field that was particularly relevant in the 1930s and 1940s in Chile, and which was built on the basis of a powerful nationalist discourse. The field in question is the field of sexual education, which is approached from the analysis of two corpuses of writings: a set of texts by Judge Samuel Gajardo, on the one hand; and a set by the Catholic psychiatrist and psychoanalyst, Manuel Francisco Beca, on the other.This analysis gives rise to a vision of the appropriation of psychoanalysis in Chile that greatly diverges from the vision that continues to be transmitted today by the official history. Psychoanalysis seems to have been as a tremendously plastic discourse, with multiple readings and applications, particularly useful in the field of prophylaxis of sexually transmitted diseases (STDs). What is mostly emphasized, is its focus on childhood and child sexuality. In stark contrast to the exclusivity that the official history of Chilean psychoanalysis has generally accorded to the clinical field, to psychiatry and to psychoanalytic institutions, what stands out here are the uses that psychoanalysis can have for socio-political and cultural projects.